1967
DOI: 10.1099/00221287-47-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Amino Acid into Protein by Utilizing a Cell-Free System from Paramecium

Abstract: SUMMARYCell-free incorporation of amino acid into paramecium protein was accomplished by using ribosomes, soluble fraction, guanosine triphosphate and adenosine triphosphate. Less than 20% of the incorporated label was detected in the soluble fraction, indicating that little if any complete de novo synthesis occurred. Incorporation was markedly decreased by submicrogram concentrations of RNase and by decreasing [Mg2+] to below 3 ,umoles/ ml. A 'pH 5 fraction ' from mouse liver was able to replace the parameciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1967
1967
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Most cell-free systems of bacterial origin require relatively high Mg+ + for optimal protein synthesis. Interestingly, Reisner & Macindoe ( 17) working with a cell-free preparation from Paramecium aurelia, and Chesters( 2 ) employing one from C. oncopelti, found that the critical [ Mg+ + ] stimulating amino-acid incorporation was -5 mlM. Our system from C. jasciculata required -10 mM Mg++ for optimal activity for I4Cleucine incorporation, and -16 mM Mg+ + when synthetic messenger (poly U) was added.…”
Section: Discussionmentioning
confidence: 84%
“…Most cell-free systems of bacterial origin require relatively high Mg+ + for optimal protein synthesis. Interestingly, Reisner & Macindoe ( 17) working with a cell-free preparation from Paramecium aurelia, and Chesters( 2 ) employing one from C. oncopelti, found that the critical [ Mg+ + ] stimulating amino-acid incorporation was -5 mlM. Our system from C. jasciculata required -10 mM Mg++ for optimal activity for I4Cleucine incorporation, and -16 mM Mg+ + when synthetic messenger (poly U) was added.…”
Section: Discussionmentioning
confidence: 84%
“…This aspect has already been discussed in detail by Reisner and Macindoe (13). The in vitro system provided more controlled conditions for the study of protein formation.…”
Section: Discussionmentioning
confidence: 85%
“…The characteristics of protein synthesis in cell-free extractso f protozoa have been investigateds ince the end of the 1950s. [54][55][56][57][58] The initial aim of these studies was examination of the translation process. Cell-free systems with ribosomes isolated from various protozoan organisms( Tetrahymena pyriformis, [55] Crithidia oncopelti, [54,56] Paramecium aurelia, [57] Entamoeba histolytica [58] )w ere investigated to characterize the incorporation efficiency of amino acids depending on buffer supplements,p H, energy sources, cation concentrations, and supplementation with spermidine or other compounds.…”
Section: Protozoan Extractsmentioning
confidence: 99%
“…[54][55][56][57][58] The initial aim of these studies was examination of the translation process. Cell-free systems with ribosomes isolated from various protozoan organisms( Tetrahymena pyriformis, [55] Crithidia oncopelti, [54,56] Paramecium aurelia, [57] Entamoeba histolytica [58] )w ere investigated to characterize the incorporation efficiency of amino acids depending on buffer supplements,p H, energy sources, cation concentrations, and supplementation with spermidine or other compounds. [54] More recently,acell-free system based on the protozoa Leishmania tarentolae [59] was established, in order to understand and characterizep arasitic proteins and their influence on parasitic biogenesis.…”
Section: Protozoan Extractsmentioning
confidence: 99%